2023
DOI: 10.1590/1807-3107bor-2023.vol37.0006
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors and treatment options for sleep bruxism in children: an umbrella review

Abstract: Data on clinical management options for sleep bruxism in the primary dentition are inconclusive. This umbrella review aimed to synthesize the available evidence from systematic reviews (SRs) on the associated factors and treatment approaches for clinical management of sleep bruxism in children. A search was conducted in the MEDLINE/PubMed, Web of Science, Embase, and OpenGrey databases up to March 2022. SRs published on sleep bruxism in children containing data on associated factors or treatment outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…2 Some associated factors are: stress, sleep characteristics, personality traits, genetics, the action of neurotransmitters and exogenous factors (such as caffeine and some medications, such as selective serotonin reuptake inhibitors). 3,4 There is a significant discrepancy in the prevalence of SB 5 in children and adolescents, ranging from 3.5% to 49.6% and this prevalence decreases with increasing age and is, therefore, lower in the adult population. [6][7][8] Bruxism is related to the attenuation of emotions 9 and, in this emotional context, bullying can be a possible associated factor.…”
Section: Introductionmentioning
confidence: 99%
“…2 Some associated factors are: stress, sleep characteristics, personality traits, genetics, the action of neurotransmitters and exogenous factors (such as caffeine and some medications, such as selective serotonin reuptake inhibitors). 3,4 There is a significant discrepancy in the prevalence of SB 5 in children and adolescents, ranging from 3.5% to 49.6% and this prevalence decreases with increasing age and is, therefore, lower in the adult population. [6][7][8] Bruxism is related to the attenuation of emotions 9 and, in this emotional context, bullying can be a possible associated factor.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiological mechanism indicates that stress, high levels of responsibility, anxiety, personality traits and neuroticism tend to release emotional tension and thus develop SB activities (Scarpini et al, 2023). These factors act as a stimulus to the central nervous system, modifying the release of neurotransmitters such as dopamine, which results in repetitive activity of the jaw muscles characterized by bruxism.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, some aspects associated with SB in adults and children can be mentioned: biological factors (genetic factors, airway obstruction, loud snoring or open‐mouthed during sleep, mental health issues, obstructive sleep apnea); neurochemicals (dopamine and other neurotransmitters); psychological factors (stress sensitivity, personality traits and anxiety). In addition, being male sex, moving a lot, being a secondhand smoker, snoring loudly, restless sleep or with a light on or noise in the room and sleeping lower than 8 h are also some associated factors involved in bruxism, abandoning past paradigms of dental occlusion (Guo et al, 2018; Lobbezoo et al, 2018; Scarpini et al, 2023). However, this previous literature has shown that there is not only one mechanism that explains the appearance of bruxism, and a multifactorial cause is present.…”
Section: Introductionmentioning
confidence: 99%